Complicated caries of permanent teeth in children: status of the problem and modern solution ways - N.S. Proshchenko; H.V. Sorochenko; O.I. Ostapko; O.M. Plyska; Yu.V. Trokhimets (Medičnì Perspektivi)
The issue of improving dental care protocols for children with multiple (decompensated) and complicated caries of permanent teeth, their full rehabilitation is particularly relevant, especially in periods of social cataclysms (the COVID-19 pandemic, martial law, etc.). The purpose of this study was an assessment of the dental caries experience, analysis of modern approaches to diagnosis, treatment, prevention and rehabilitation of complicated caries of permanent teeth among children in Kyiv. The material of the study was data from medical histories of 236 children aged 7-18 years. During the analysis of the obtained data, the dental caries experience, % of cases of toothache complaints and part of the need for replacement or correction of restorations after the treatment of complicated caries were calculated. The prevalence of caries of permanent teeth among 7-18-year-old children (n=236) in the period 2020-2023 was 42-95%, the dental caries experience – 1.73-6.4, the frequency of diagnosis of complicated caries – 4.8-37,1%, the prevalence of toothache – 31%, the part of the need for replacement of restorations after treatment of complicated caries – 62%. The obtained indicators confirm the absence of a downward trend compared to similar data for more than 15 years of observation. Diagnosis, treatment and full rehabilitation of complicated caries of permanent teeth in children is complex, multi-stage and requires the practical experience and patience of a dentist and the usage of the most modern materials and technologies. To date, there are no clear scientifically based protocols for the restoration of permanent teeth, in particular with incomplete root formation, after endodontic treatment. The usage of modern technologies of orthopedic dentistry and materials science (3D scanner, 3D printer, T-scan, polymers) will allow to significantly improve the quality of comprehensive treatment and rehabilitation of children with complications of caries of permanent teeth.